Enhanced tumor suppression in colorectal cancer via berberine-loaded PEG-PLGA nanoparticles - Shen, Fei; Zheng, Yun-Sheng; Dong, Lan; Cao, Ziyang; Cao, Jie (Frontiers in Pharmacology, 2024)
Colorectal cancer (CRC) stands as the third most widespread cancer globally with poor prognosis. Berberine (Ber), as one herbal phytochemical, showed promise in CRC therapy, but its exact mechanism is unclear. Small molecule traditional drugs face challenges in quick metabolism and low bio-availability after systemic administration. Nanodrug deliver system, with their unique properties, has the advantages of protecting drugs, improving drug bio-availability, and reducing toxic and side effects, which exhibited huge drug delivery potential. Herein, the PEG-PLGA nanocarrier was used for encapsulated Ber according to nanoprecipitation and obtained nanomedicine, denoted as NPBer. In vitro, the flow cytometry test and CCK8 assays indicated that NPBer was more easily taken up by HCT116 CRC cells, and had stronger inhibition on cell proliferation with the increase of drug concentration. In addition, RNA-Seq was employed to explore the alterations in the transcriptomes of cancer cells subsequent to treatment with Free Ber or NPBer.The sequencing results indicate that Ber could activate cellular aging mechanisms, intensified the iron death pathway, optimized oxidative phosphorylation efficiency, exacerbated apoptosis, accelerated programmed cell death, and negatively modulated key signaling pathways in CRC cells including Wnt, TGF-beta, Hippo, and mTOR signaling pathways. Based on PEG-PLGA nanocarriers, NPBer can improve the in vivo delivery efficiency of Ber, thereby enhancing its antitumor efficacy in vivo, enhancing apoptosis by enhancing the mitochondrial autophagy and autophagy activities of CRC cells, negatively regulating the inflammatory mediator to regulate TRP channels, and inhibiting the activation of Notch signaling pathway. In vivo, Ber after being encapsulated by nanomaterials can significantly improve its accumulation and durable drug targeting in tumor site, resulting in induce maximum cell apoptosis and effectively inhibit the proliferation of HCT116 tumor. This strategy provided a promising antitumor therapeutic strategy using Ber-based drugs..